MicroRNAs and ceRNAs: therapeutic implications of RNA networks. (September 2014) - Giza, Dana Elena; Vasilescu, Catalin; Calin, George A
<x xml:space="preserve">Abstract</x> Introduction: A new concept of gene regulation, in which competitive endogenous RNAs (ceRNAs) compete for common microRNAs (miRNAs), suggests that mRNA targets have an active role as key elements in the regulation of miRNA availability within cells. ceRNAs are considered to be natural decoys of miRNA activity and can influence the expression of multiple miRNAs. Areas covered: A new complex network of indirect interaction among the RNA transcripts competing for the same pool of miRNAs has been described; in this network, the nodes are the targets, and the links between the nodes are the miRNAs the targets have in common, which form smaller subnetworks. The incidence, state and severity of cancer can be evaluated on the basis of this network signature. The study of these new genome-scale regulatory networks involving miRNAs and ceRNAs may provide information that researchers can use to fine-tune these networks to improve responses to cancer therapy and/or develop new therapeutic interventions. Expert opinion: Combinational approaches based on complex regulatory ceRNA networks (ceRNETs) may be one of the most promising strategies for silencing important mediators of cancer-promoting pathways. Targeting a single miRNA may in fact represent a combined intervention that acts on the feedback and compensatory pathways that can impair treatment response or cause treatment resistance.